Natural variation in transcriptional rhythms modulates photoperiodic responses. (May 2015) - Kubota, Akane; Shim, Jae Sung; Imaizumi, Takato
Abstract : Recent studies have demonstrated that allelic variation in daily expression profiles of the GIGANTEA gene may account for the variance in plant growth in different accessions. Studying natural variation in daily transcriptional patterns of circadian-clock regulated genes provides new insights into plant adaptive strategies to different geographical regions.